2013
DOI: 10.1021/bm400658k
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of G-Block Distributions and Their Impact on Gel Properties of in Vitro Epimerized Mannuronan

Abstract: 2 This paper reports a study of the distribution and function of homopolymeric guluronic acid blocks (G-blocks) in enzymatically modified alginate. High molecular weight mannuronan was incubated with one native (AlgE6) and two engineered G-block generating mannuronan C-5 epimerases (AlgE64, and EM1). These samples were found to contain G-blocks with a DP ranging from 20 to approximately 50, lacking the extremely long G-blocks (DP>100)found in algal alginates Calcium gels from epimerised materials were highly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…The molecular weights of the chitosans were estimated from the determined [η] using the Mark-Houwink-Kuhn equation with the reported parameters [59]. The molecular weights of the alginates were determined as reported [60]. The parameters of the chitosan and alginate samples are summarized in Table 1.…”
Section: Biopolymer Samplesmentioning
confidence: 99%
“…The molecular weights of the chitosans were estimated from the determined [η] using the Mark-Houwink-Kuhn equation with the reported parameters [59]. The molecular weights of the alginates were determined as reported [60]. The parameters of the chitosan and alginate samples are summarized in Table 1.…”
Section: Biopolymer Samplesmentioning
confidence: 99%
“…In a previous paper we reported that gels made from in vitro epimerized poly-M lacks the fraction of very long G-blocks that are ever-present in brown seaweed alginates and thereby display an unusually low Young's modulus and a high degree of syneresis. 22 In this study, we compare the G-block distributions and gel properties of A. vinelandii alginate with in vitro epimerized poly-M and brown seaweed alginate. Data on the epimerization pattern obtained by epimerization with full length AlgE1, as well as its individually active G-block forming A-modules is also presented.…”
Section: ■ Introductionmentioning
confidence: 99%
“…VLG is an important factor since alginate gels made from poly-M in vitro epimerized with AlgE6 in the range of 29−68% G all has a syneresis between 60 and 70%, despite a low amount of alternating sequences,22 while gels made from deacetylated A. vinelandii alginate has a syneresis below 40%.Altogether, the differences in G-block distribution (Figure 3) and syneresis (Figure 4B) between AlgE6 epimerized poly-M and A. vinelandii alginates shows that the latter contains a fraction of VLG. This results in a different organization of the hydrogel network than the short to intermediate length Gblocks found in AlgE6 epimerized poly-M. As expected the presence of O-acetyl groups impairs gel formation, giving weaker gels.…”
mentioning
confidence: 99%
“…Although the intrinsic inflexibility of the alginate chain increases in the order MG Ͻ MM Ͻ GG (4), the selectivity for binding of cations and gel-forming properties is mainly linked to the G-blocks (3,5,6). Recently, it has been shown that G-blocks larger than 100 consecutive residues are essential for forming stable calcium gels (7).…”
mentioning
confidence: 99%